A Review Evaluation of Increasing Number of Somatic Cells in Milk Quality and Its Compounds - Ahmadi, Sayed Arif (Journal of Natural Sciences – Kabul University, 2025)
Milk is one of the most complete and essential natural foods for humans, and dairy products can be used for people of all ages. Healthy milk production and quality are crucial for protecting the health of consumers. One of the most important indicators for evaluating the quality and safety of milk is mastitis, which leads to changes in milk compounds. The somatic cell count (SCC) is important to dairy producers because high counts can lead to poor quality and affect the physicochemical properties of milk, such as protein, fat, lactose, and total solids. Thus, it is necessary to ensure that milk and its products are free from contamination and changes in milk composition.